Culinary Culture Construction in Indonesian Master Chef Show at RCTI - rosalia nurdiarti (JCommsci - Journal Of Media and Communication Science, 2019)
This research aims to uncover the construction of culinary culture, on the empirical level that presents a socio-political reality, where 'food' can trigger a constellation of interests over the power of certain groups. At the level of ‘symbolic’ food represents identity, language, culture and construction of reality. This phenomenon is symbolically present through television media, one of which shows the cooking competition of Indonesian Master Chef. This research uses textual analysis. By using Norman Fairclough's critical discourse analysis to uncover the construction of culinary culture in the Indonesian Master Chef program. This analysis uses three stages of practice of citizenship at the micro level (audio visual text), meso (consumption and production of text) and macro (connecting text networks with social conditions). The analysis of selected scenes reveals that: at the level of the text, culinary culture is present through menus with European and American tastes. The construction of discourse built on the process of consuming text reveals that, culinary culture reaps the "perception" of "best" taste in European and American cuisine.